Understanding risk‐based licensing schemes for alcohol outlets: A key informant perspective. (16th February 2020) - Miller, Peter G.; Curtis, Ashlee; Graham, Kathryn; Kypri, Kypros; Hudson, Kate; Chikritzhs, Tanya
Abstract: Introduction and Aims: Risk‐based alcohol licensing (RBL) has been introduced in several jurisdictions in Australia, New Zealand and Canada with the intention of reducing harm in and around alcohol outlets. RBL involves tailoring licence fees or regulatory agency monitoring levels according to risk criteria such as trading hours, venue size and compliance history. The aim of this study was to document key informant perspectives including their perceptions of the purpose of RBL, how it works and its active ingredients. Design and Methods: We conducted semi‐structured in‐depth interviews with 28 key informants, including four government policy makers, four liquor licensing representatives, four local council members, eight police officers, six licensees, one academic and one community advocate from Victoria, Queensland, the Australian Capital Territory and Ontario, Canada. We analysed the transcripts using a thematic approach. Results: Informants varied in their opinions about whether RBL achieved its objective of reducing alcohol‐related harm. They identified difficulties in enforcing the compliance history component of the scheme due to loopholes in legislation as a major shortfall, and the need to apply RBL to packaged liquor (off‐licence) outlets. They also discussed the need to consider outlet density associated with the location of a venue when assessing venue risk. Discussion and Conclusions: RBL schemes vary by jurisdiction and emphasise different components. In general, informants surmised that RBL as implemented has probably had little or no preventive effect but suggested that it may be effective with greater monitoring and penalties large enough to deter bad practice.